Investigating the structure of disordered eating symptoms in adult men: A network analysis - Eschrich, R. Leopold; Halbeisen, Georg; Steins‐Loeber, Sabine; Timmesfeld, Nina; Paslakis, Georgios (European eating disorders review : the professional journal of the Eating Disorders Association)
Objective Eating disorders (EDs) increasingly emerge as a health risk in men, but there is concern that men's symptoms go unnoticed due to stereotypical perceptions and gender-related differences in symptom presentation. Novel assessments focused particularly on attitudes and behaviours towards increasing muscle size and definition. Using network analysis, this study aimed to corroborate and extend previous findings on disordered eating presentation in men by examining the role of muscularity concerns among an extended range of disordered eating symptoms. Method N = 294 adult men (18 years or older) completed muscularity-related and disordered eating assessments, among which we included assessments for orthorexic eating and Avoidant/Restrictive Food Intake Disorder for the first time. We selected symptoms empirically, estimated a regularised network, identified symptom communities, evaluated network loadings and bridge centrality estimates, and compared network structures between different groups of participants. Results We identified five symptom communities related to muscularity-related concerns, features of core ED psychopathology, and selective eating. Symptoms regarding ruminating about healthy eating, guilt for unhealthy eating, weight overvaluation, concerns about muscularity, and selective eating emerged as highly central. Discussion The results largely corroborate previous observations but suggest that muscle-building behaviours are part of a broader cluster of male body shaping and rule-based dieting behaviours.
Keywords: drive for muscularity; eating disorders; men; psychotherapy; thinness ideal